Optimization of HPMC and Glycerine in Essence of Sheet Mask Containing Centella asiatica (L.) Urb. Extract and Snail Mucus (Achatina fulica) as A Moisturizer - Anjani Saskia Putri; Endang Diyah Ikasari; Ungsari Rizki Eka Purwanto (Journal of Food and Pharmaceutical Sciences, 2024)
Various natural ingredients have been formulated as moisturizers in cosmetics, both from natural and animal raw material, especially Centella asiatica (L.) Urb. Extract and snail mucus (Achatina fulica). However, there is only a little research to determine the development of both material in one cosmetic preparation, namely sheet mask. The mask sleeve, which is a sheet mask applicator, will dry longer than other masks, therefore the penetration shown as a moisturizer is better. Gelling agents (such as hydroxypropyl methyl cellulose (HPMC)) and humectants (such as glycerinee) are important ingredients in sheet masks. This research aims to optimization HPMC and glycerine in a sheet masks Centella asiatica and snail mucus. Optimization of HPMC and glycerine with a ratio of 0.3–3% HPMC and glycerine was carried out using the Design Expert 10 with Simplex Lattice Design method. The responses from optimization of the preparation were pH, viscosity, absorption power and skin moisture. The optimum formula was obtained at a concentration of 0.589% HPMC and 2.711% glycerine with pH of 5.64 ±0.02; viscosity of 4581.8± 59.80 cPs, absorption power in scale of 4.6+0,55 , and skin moisture of 32.09%+3.21. The irritation test has a score of 0 or does not cause irritation.